Total Quality Management (TQM) dalam Pelaksanaan Program-Program Berbasis Karakter Religius - Samsul Maarif; Eliyanto Eliyanto (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2020)
Total Quality Management is a reference in education in educational institutions based on the quality of processes, services, human resources and results. Management consists of several things including: planning, implementation, evaluation and follow-up. Schools which strengthen religious character are efforts to develop education to realize national education in the midst of globalization. Often with that also the demands of society want higher quality education not only in the academic field (cognitive and psychomotor), but in the field of morals, character or character (affective). This research is to describe the application of TQM in strengthening religious character consisting of customers, teamwork and continuous improvement. This study uses a qualitative descriptive approach, with the method of observation, interviews and documentation. The research subjects were school principals, vice principals, educators, education staff, students and student guardians. Data validity with triangulation. Analysis is Miles and Huberman's interactive analysis model through data collection, data reduction, data presentation, and conclusions. In general, this research shows that in the implementation of TQM it must: (1) Focus on customers, namely serving all the needs of students, educators, educational staff, guardians of students and the community, (2) implementation of strengthening religious character integrated with intracurricular, co-curricular, extra-curricular activities and habituation, (3) Evaluation in the form of an integrated attitude in each daily assessment, midterm assessment, final semester assessment, and grade promotion examination, (4) teamwork is carried out by involving and empowering all components of the school, both educators and education staff, ( 5) continuous improvement includes: The use of the new National curriculum, improvement of academic and educational staff performance, as well as improvement of supporting physical facilities and infrastructure.